Leadership performance engineering chairpersons as influenced by their personal attribute - Constantino, John Leonard M. (Pangasinan : [s.n.], 2017)
This descriptive research aimed to determine the leadership performance of the College of Engineering Department Chairpersons of selected State Universities and a College in Region III as perceived by themselves and by their faculty members. Among the factors considered for personal attributes were the number of years as academic chairperson, highest degree earned, seminars/trainings attended related to management for the last three years and performance evaluation for the past three years. On the other hand, leadership performance included planning, organizing, leading, and controlling.
Bibliography: pages 99-105.
CHED-La Union
Keywords: Personnel management